Novel Susceptibility Loci for Moyamoya Disease Revealed by a Genome-Wide Association Study. Issue 1 (January 2018) - Duan, Lian; Wei, Ling; Tian, Yanghua; Zhang, Zhengshan; Hu, Panpan; Wei, Qiang; Liu, Sugang; Zhang, Jun; Wang, Yuyang; Li, Desheng; Yang, Weizhong; Zong, Rui; et al.
Abstract : Background and Purpose—: Moyamoya disease (MMD) is a rare cerebral vasculopathy characterized by bilateral internal carotid artery stenosis and often leads to stroke in children or young adults. Although familial inheritance is well recognized, the genetic basis of MMD remains poorly understood. Methods—: A 2-stage genome-wide association study was conducted involving 1492 cases and 5084 controls. In the discovery stage, logistic regression was used to test associations, and imputation was conducted based on genotyped single-nucleotide polymorphisms (SNPs). In the validation stage, the top significant SNPs were again genotyped in an independent cohort. Fixed-effects inverse variance-weighted meta-analysis was used in the combined discovery and validation samples. Furthermore, association analysis was conducted in subgroups using patient clinical data. Results—: The study identified 10 novel risk loci with genome-wide significance ( P <5×10 −8 ) and confirmed a previously reported locus on 17q25. No significant SNP showed evidence of heterogeneity between the 2 stages. Cumulatively, these SNPs explained 14.76% of disease risk variance—a substantial proportion of the 39.02% of risk variance explained by all genome-wide genotyped SNPs. One SNP, rs9916351 in RNF213 ( P combined =4.57×10 −54 ; odds ratio, 1.96), showed a stronger genetic effect on early-onset than late-onset MMD ( P =0.003). Two novel SNPs in genes regulating homocysteine metabolism, rs9651118 in MTHFR ( P combined =2.49×10 −19 ; odds ratio, 0.65) and rs117353193 in TCN2 ( P combined =6.15×10 −13 ; odds ratio, 1.43), were associated with high-serum homocysteine in MMD cases. Additionally, another SNP associated with MMD (rs2107595 in HDAC9 ; P combined =1.49×10 −29 ; odds ratio, 1.64) was previously implicated in large-vessel disease. Tissue enrichment analysis showed that the genes of associated loci were highly expressed in the immune system (false discovery rate, <0.05). Conclusions—: This study identifies several novel susceptibility genes for MMD. The association with homocysteine metabolism and the immune system enrichment of susceptibility gene expression suggest that therapeutic interventions targeting these pathways may be effective approaches for MMD treatment. Abstract : Supplemental Digital Content is available in the text.